2022
DOI: 10.1007/s12144-022-03942-x
|View full text |Cite
|
Sign up to set email alerts
|

Is it worth being attached to the leader? Transformational leadership and various types of performance: The mediating role of leader as attachment figure

Abstract: We assumed that the perception of the leader as an attachment figure would mediate the relationship between transformational leadership transformational leadership and leader/follower's reports of team performance. Leaders (N = 38) and employees (N = 204) completed separate questionnaire batteries. Team members assessed their perceptions of the leader as an attachment figure, transformational leadership of their leaders, and general and citizenship performance. Leaders assessed their transformational leadershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The positive model of others in the form of a relationship with the leader supports the positive model of others in the form of colleagues. When workers perceive the leader as an attachment figure, they tend to cooperate more with other teammates Lisá & Greškovičová, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive model of others in the form of a relationship with the leader supports the positive model of others in the form of colleagues. When workers perceive the leader as an attachment figure, they tend to cooperate more with other teammates Lisá & Greškovičová, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Mental representations of attachment models can overlap, but they are still different (Dugan et al, 2022;Klohnen et al, 2005;Lisá & Greškovičová, 2022;Overall et al, 2003). In the work context, the domain-specific models of work relationships are different from other domain models (Greškovičová & Lisá, 2023).…”
Section: Introduction Adult Attachment and Attachment In The Workplacementioning
confidence: 99%
“…Drawing on the leadership-followership literature, managers are key factors in predicting subordinates' behavior and individual leadership emergence [12]. For instance, supervisors can affect employees' behavior via charisma, using inspirational motivation, and shaping their goal orientations [13,14]. Furthermore, prior research has also suggested that although leadership emergence is often driven by individual differences (e.g., gender [15]; self-efficacy [16]; personality [17]; competency [18] and intelligence [19]), managers, as an important contextual factor, play a critical role in facilitating it [20].…”
Section: Introductionmentioning
confidence: 99%
“…Today, no one doubts that the application of adult attachment to the organizational context has value and sense. Many studies explored adult attachment in relation to organizational behavior and outcomes at the individual, team, and/or organizational levels ( Davidovitz et al, 2007 ; Harms, 2011 ; Yip et al, 2017 ; Grady et al, 2019 ; Lisá and Greškovičová, 2022 ). Despite the emerging option of transferring adult attachment to the organizational setting, we need to face serious questions and possibly doubts.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding mental illness, attachment to the leader is related to followers’ burnout ( Lavy, 2014 ). Furthermore, the transformational leader as an attachment figure also promoted performance at the team level ( Lisá and Greškovičová, 2022 ). However, not only is leadership style important for organizational, group, and follower outcomes, but the personality of leaders is also relevant ( Antonakis et al, 2012 ; Blake et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%